2021
DOI: 10.3390/genes12050616
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Profile of Breast Cancer in Germline ATM and CHEK2 Mutation Carriers

Abstract: The most common breast cancer (BC) susceptibility genes beyond BRCA1/2 are ATM and CHEK2. For the purpose of exploring the clinicopathologic characteristics of BC developed by ATM or CHEK2 mutation carriers, we reviewed the archive of our Family Cancer Clinic. Since 2018, 1185 multi-gene panel tests have been performed. Nineteen ATM and 17 CHEK2 mutation carriers affected by 46 different BCs were identified. A high rate of bilateral tumors was observed in ATM (26.3%) and CHEK2 mutation carriers (41.2%). While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 65 publications
4
22
1
Order By: Relevance
“…If ATM is synthesized it will lack most of the protein sequence and thus be non-functional. Interestingly, a recent study that explored the clinico-pathologic characteristics of breast cancers developed by ATM mutation carriers reported the median age at first diagnosis to be 46.9 years in their cohort 18 . Unfortunately we do not have any further histopathologic information on the breast cancer of BRB14.…”
Section: Discussionmentioning
confidence: 99%
“…If ATM is synthesized it will lack most of the protein sequence and thus be non-functional. Interestingly, a recent study that explored the clinico-pathologic characteristics of breast cancers developed by ATM mutation carriers reported the median age at first diagnosis to be 46.9 years in their cohort 18 . Unfortunately we do not have any further histopathologic information on the breast cancer of BRB14.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria consisted of histology-proven BC patients with multigene panel test for hereditary cancers, pre-operative breast and axillary US, complete surgery, pathology and immunohistochemistry reports. We excluded patients who refused surgery (12) or had incomplete US images (5) or unavailable axillary pathology reports (3). Currently, the genetic testing is indicated in our institution if at least one of the following criteria are met: one first-degree relative with BC diagnosed < 50 years or two second-degree relatives with BC diagnosed < 50 years, age < 35 years at diagnosis, triple-negative subtype or bilateral breast cancer; and if additional melanoma, colon, pancreas or ovarian cancer is present in the patient's personal history or that of their relatives.…”
Section: Methodsmentioning
confidence: 99%
“…Limited data are available regarding the role of axillary US in high-risk breast cancer patients. Studies suggest that patients with pathogenic mutations (such as BRCA1, BRCA2, ATM or CHEK2) are more prone to have axillary metastasis, related to their highly aggressive breast cancers [10][11][12]. However, no imaging modality was evaluated nor reported in identifying them.…”
Section: Introductionmentioning
confidence: 99%
“…ATM and CHEK2 are recognized as the most common breast cancer susceptibility genes, and their attenuation is associated with BRCAness, namely phenocopies of BRCA1/2 defects. In a single institutional review of 1185 breast cancer cases using multi-gene panel testing (MGPT), a high occurrence of bilateral tumors was observed in 26.3% of the ATM germline variant carriers and in as much as 41.2% of CHEK2 variant carriers [ 26 ]. Histological analyses of breast cancer subtypes showed that there were varying trends between ATM and CHEK2 .…”
Section: Molecular Components and Cascade Overview Of Hrmentioning
confidence: 99%
“…Lobular carcinoma was observed in 21.4% of CHEK2 -related invasive tumors. A quarter of ATM-related breast cancer and approximately one-third (30%) of CHEK2 -related breast cancers were in situ carcinomas [ 26 ].…”
Section: Molecular Components and Cascade Overview Of Hrmentioning
confidence: 99%